Dynamic responses of 500-kV transmission line towers under impact force of rockfall in a mountainous area - Linping, Yue; Feng, Jiang; Hong, Jiang; Wei, Jiang; Zhiyong, Wang; Zheng, Zhou; Jianping, Xiong; Tian, Wu (Frontiers in Mechanical Engineering, 2022)
Since most of the UHV/EHV transmission lines pass through mountainous areas, the impact of rocks caused by landslides or collapses may cause partial deformation of the iron tower, or even collapse, seriously threatening the safety operation of transmission lines. To analyze the dynamic response characteristics and influencing factors of the rolling rock impacting the transmission line tower, a simulation model for 500kV steel suspension tower impacted by falling rock was established by finite element analysis software LS-DYNA in this paper, and dynamic response characteristics of the rolling-rock impacting the steel tower was analyzed under different conditions. Results show that the stress on the tower foundation is closely related to the mass, volume and initial velocity of the rolling stone. Under the same rolling stone speed, the stress on the tower foundation increases as the mass of the rolling stone increases. The maximum increase in stress peak generated between the two can reach 110%; when the rolling stones of the same size collide with different initial velocities, the location and magnitude of the peak stress of the tower foundation are different. When the initial speed of the rolling stones is more remarkble than 15m/s, the tower foundation The hit area increased significantly, causing the tower base to be directly destroyed.